UV Cured Polymeric Optical Fluorescence Sensor for the Determination of Au (III) - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR; ÇUBUK, SONER (WILEY-V C H VERLAG GMBH, 2014)
The recognition and sensing of the biologically and environmentally important metal ions has emerged as a significant goal in the field of chemical sensors in recent years. Among the various analytical methods, fluorescence has been a powerful tool due to its simplicity, high detection limit and application to bio imaging. In this study, UV cured polymeric optical sensor for Au (III) ion based on a fluorescence membrane has been developed. The response characteristics of the sensor including dynamic range, pH effect and response time were systematically investigated. The influences of the conditions such as pH, response time on the metal ion binding capacity of membrane were also tested.
Keywords: Au (III); fluorescence spectroscopy; membrane; optical sensor; UV-curing; GOLD